KARAKTERISTIK FLAKE UBI JALAR ORANGE DAN UNGU DENGAN PENAMBAHAN MINYAK NABATI (MINYAK SAWIT, MINYAK KELAPA, DAN MARGARIN) - Avinda Nur Rahmawati; Maryanto Maryanto; Nurhayati Nurhayati (Faculty of Agricultural Technology, University of Jember, 2019)
Sweet potato flake is ready-to-eat foods comsumed by the adding a milk. Lipid or oil in the flake can change the crunchy and texture. Oil was added to fungtions as the stabilisator, lubricant and to improved crispness of flake. The aims of this study was to evaluate of physical and sensory characteristic of flake made from orange and purple sweet potatoes with addition the vegetable oils. This study used Complete Random Design (CRD) with two factors and two replications. The A factor was type of sweet potatoes, i.e. orange sweet potato (A1) and purple sweet potato (A2). The B factors (B) were type of oils; palm oil (B1), coconut oil (B2) and margarine (B3). The results showed that the rehydrations flake of orange and purple sweet potatoes with additions of variation oil type ranged from (58,13 - 85,61%,); hygroscopicity ranged (6,93 - 8,86%); water content ranged from (3,57 - 6,47%). The highest favorite value of color on orange sweet potato flake with addition margarine (5,42), while purple sweet potato flake with addition palm oil has the lowest favorite value (3,46). The aroma value of orange and purple sweet potatoes flake with the addition coconut oil has the highest (5,15) and (5,35) than palm oil and margarine. Preference taste of orange and purple sweet potatoes flakes was the highest if additions of coconut oil, i.e. very like (score 5,12). Crispness preference was preferred from orange sweet potato flake with coconut oil additions (4,96). Favorite taste was preferred on purple sweet potato flake with coconut oil addition (5,38). Keywords: coconut oil, flake, preference test, sweet potato, vegetable oil